Effects of 5-Gy irradiation on fertility and mating behaviour of Nezara viridula (Heteroptera: Pentatomidae) - Žunič, Alenka (Radiology and oncology (Ljubljana), 2002)
Background. The polyphagous and cosmopolitan species Nezara viridula is one ofthe most important insect pests. The sterile insect technique (SIT) is a pest control strategy that involves sterilising males by exposing them to ionising radiation. Sterile males, released into wild population, mate with females, but eggs are not fertilised and the population gradually declines. Exposing insects to radiation during their growth stage might require lower sterilising dose. The aim of our study was to test whether 5-Gy irradiation of5th instar nymphs significantly affects: (1) moulting and further development of the irradiated nymphs, (2) the male's and female's reproduetivesystem and (3) the mating competitiveness of treated males, with special focus on vibrational communication. Methods: The 5th instar nymphs were irradiated with 5 Gy using X ray generator and monitored daily. Results: The observed effects of irradiation were: prolonged moulting increased mortality during development and during the first day of adult life, decreasedmales to females ratio, decreased fecundity, egg production, proportion of fertile eggs and progeny survival. The reaction of a male to stimulation with the model female calling song was tested. The irradiated and non-irradiated males responded to stimulation with emission of the eourtship song (MCrS). Temporal parameters of MCrS emitted by non-irradiated males differed when compared with those of irradiated ones. Conclusions: The 5-Gy irradiation of 5th instar nymphs did not affect mating behaviour. However since the irradiation during growth stage decreased the fertility and fecundity of emerged adults, this technique, in combination with certain othersuppression teehniques, could be a successful control strategy for management of Nezara viridula. On the other hand observed effects on moulting and further development of the irradiated nymphs could decrease the efficiencyand application of this strategy.
Keywords: Animal Communication; Gryllidae; Insect Control; insekti; Insekti, nadzor; Levitev; Molting; pest; radiacija; Radiation Effects; sterilnost; škodljivci; Vibracija; Vibration; Žival komunikacija